NUTQ KO'NIKMALARINI O'QITISHDA CHET TILI DARSLARIDA INNOVATSION TEXNOLOGIYALARNI QO'LLASH - Qaxorova Tursunoy Ulug’bek qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract. The article deals with the necessity and the importance of applying innovative technologies to foreign language lessons in teaching speaking skills. They have a number of advantages compared with other technology in the field of learning a foreign language, as they allow: to improve the process of organic combination of traditional forms and methods of education with nnovation; implement training, information, games, modeling, design and analysis functions; general didactic perform such principles as the visibility, accessibility, difficulty feasible, system, transition from education to self-education, positive emotional background of training, between theory and practice.